Significance of combined detection of LunX mRNA and tumor markers in diagnosis of lung carcinoma - Yu, Hui; Huang, Xiuying; Zhu, Zhihua; Hu, Yi; Ou, Wei; Zhang, Lanjun; Zhou, Ningning (Chinese Journal of Cancer Research; Vol 26, No 1 (February 27, 2014): Chinese Journal of Cancer Research, 2014)
Objective: To evaluate the significance of combined detection of LunX mRNA, carcinoembryonic antigen (CEA), neuron-specific enolase (NSE), and cytokeratin 21-1 fragment (CYFRA21-1) in clinical diagnosis of lung carcinoma. Methods: Based on the quantitative RT-PCR and chemiluminescence immunoassay, the expression levels of LunX mRNA, CEA, NSE, and CYFRA21-1 in 113 patients with lung carcinoma (case group) and 30 healthy participants (control group) were detected. Meantime, the sensitivity, specificity, and accuracy of the combination detection were also explored. Results: The positive rates of LunX mRNA in peripheral blood and CEA, NSE, and CYFRA21-1 in serum were significantly higher in case group than those in control group (χ2=17.295, 16.825, 19.148, and 17.450; P0.05). The positive rate of LunX mRNA in stage I + II, III, and IV had a significantly increasing tendency (χ2=10.565, 32.462, P